Research Technical-Operating Materials - Magdiev Shovkat Pulatovich (Zien Journals, 2022)
Motor oils have a set of physical and chemical properties established by the relevant regulatory documents that characterize its operational purpose.
Keywords: oils; Motor; operational; chemical